BATAS KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL DAN KEPOLISIAN DALAM PENINDAKAN PELANGGARAN LALU LINTAS DAN ANGKUTAN JALAN - Riswanty, Putu Yuni (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
The State of Indonesia is a state of the rule of law (rechtstaat) based on Pancasila. As a state based on law, Traffic and Road Transportation under Law No. 22/2009 is an integrated system consisting of Traffic, Road Transportation, Traffic and Road Transportation Networks, Infrastructure of Traffic and Road Transportation, Vehicles, Drivers, Road Users, as well as management thereof. Motor Vehicle Inspection Authority on the Road by the Civil Servant Investigators in the field of Traffic and Road Transportation and the Indonesian National Police Investigators incidentally is an examination of the evidence of passed test for vehicles compulsory tested, physical motor vehicles, haulage, method of transporting goods and/or transport operating license. In order to carry out its duties and functions, Civil Servant Investigators should always coordinate with the Indonesian National Police as a coordinator and supervisor of the Civil Servant Investigators. Investigators of the Indonesian National Police, as the coordinator and supervisor, implement guidance and supervision of the Civil Servant Investigators in the field of Traffic and Road Transportation. The research is classified into normative legal research using a statute approach and conceptual approach.
Keywords: Authority; Competency; Civil Servant Investigators; Traffic and Road Transportation